Peran Komunitas Buku The Diversitea dalam Meningkatkan Kesadaran Inklusi Sosial Melalui Membaca Buku Diverse - Isnaini, Aulia; Pramudyo, Gani Nur (Sabda: Jurnal Kajian Kebudayaan, 2025)
Despite being a country filled with the diversity of its people, the lack of social inclusion in Indonesia is still quite concerning. Diverse book, book who tells a story of diverse experiences, can be used as a way to build a social inclusion awareness. The Diversitea book club, a book community who introduced the importance of reading diverse books to the Indonesian readers, could play a role in increasing the social inclusion awareness. The main objective of this qualitative study was to analyze the role of The Diversitea book club, a book community whose activities centered on diverse books, in increasing social inclusion awareness. Data were collected from online observations, semistructured online interviews, and document analysis, then analyzed through the lens of qualitative data analysis by Miles and Huberman. The analysis revealed that the activities done by The Diversitea book club have fulfilled the four roles of a book community; encouraging reading, building social relationships between members, a place to discuss and share information, and supporting the wellbeings of individuals. The finding suggests that reading and discussing diverse book could help in increasing social inclusion awareness, and the nature of knowledge sharing in Communities of Practice such as The Diversitea making them a great example for organizations with similar goal; such as the public libraries in Indonesia who need to implement the Social Inclusion-Based Library Transformation program.